VESTIGE: Adjuvant Immunotherapy in Patients With Resected Esophageal, Gastroesophageal Junction and Gastric Cancer Following Preoperative Chemotherapy With High Risk for Recurrence (N+ and/or R1): An Open Label Randomized Controlled Phase-2-Study - Smyth, Elizabeth; Knödler, Maren; Giraut, Anne; Mauer, Murielle; Nilsson, Magnus; Van Grieken, Nicole; Wagner, Anna Dorothea; Moehler, Markus; Lordick, Florian (Frontiers in Oncology, 2020)
Perioperative chemotherapy plus surgery is one recommended standard treatment for patients with resectable gastric and esophageal cancer. Even with a multimodality treatment more than half of patients will relapse following surgical resection. Patients who have a poor response to neoadjuvant chemotherapy and have an incomplete (R1) resection or have metastatic lymph nodes in the resection specimen (N+) are especially at risk of recurrence. Current clinical practice is to continue with the same chemotherapy in the adjuvant setting as before surgery. In the phase II randomised EORTC VESTIGE trial (NCT03443856), patients with high risk resected gastric or oesophageal adenocarcinoma will be randomised to either adjuvant chemotherapy (as before surgery) or to immunotherapy with nivolumab and low dose ipilimumab (Nivolumab 3 mg/kg IV Q2W plus Ipilimumab 1 mg/kg IV Q6W for 1 year). The primary endpoint of the study is disease free survival, with secondary endpoints of overall survival, safety and toxicity and quality of life. This is an open label randomized controlled multi-center phase-2 superiority trial. Patients will be randomised in a 1:1 ratio to study arms. The trial will recruit 240 patients; recruitment commenced July 2019 and is anticipated to take 30 months. Detailed inclusion/exclusion criteria, toxicity management guidelines and statistical plans for EORTC VESTIGE are described in the manuscript.